Power Performance Evaluation of Standalone Renewable Energy Source Energy Management Using Pass Filter - Indah Sulistiyowati; Jamaaluddin Jamaaluddin; Izza Anshory (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Hybrid energy storage systems have shown promise in enhancing solar panel systems reliability and efficiency. However, managing the power distribution balance with multiple energy storage units remains a challenge. This research addresses power distribution balancing during solar irradiation intermittency by employing a first-order filter with lowpass and highpass characteristics. The study aims to investigate energy and power management issues for off-grid electrical systems using this filter. Results from numerical simulations and experiments with a hybrid energy storage setup comprising a battery and supercapacitor show that the first-order filter effectively allocates the first-order signal to the main energy storage and subsequent orders to the supporting energy storage. During increased intermittency, the battery contributes 62 W and stores 387 W, while the supercapacitor contributes 167 W and stores 297 W. Conversely, during reduced intermittency, the battery stores 390 W and contributes 62 W, and the supercapacitor stores 295 W and contributes 164 W. The findings demonstrate the filter's efficacy in optimizing power distribution balance within hybrid energy storage systems. However, using the supercapacitor as the main energy storage does not result in higher power efficiency compared to the battery. In conclusion, the First Order Filter presents a viable solution for addressing power distribution challenges in hybrid energy storage systems, contributing to improved energy and power management for off-grid electrical systems. Further research on cost-effectiveness, maintenance, and environmental impact is warranted for practical implementation